The Main Electorate of Right-Wing Populist Parties in Europe: Cases of the Alternative for Germany and the Freedom Party of Austria - Dmitry Yu. Meshcheryakov (RUDN Journal of Political Science, 2022)
There is an ongoing political debate on whether certain groups can be considered the electoral backbone of right-wing populist parties. On the one hand, it is argued that there is no concept of a “typical voter” for right-wing populists; on the other hand, some studies of election campaigns in different countries show that it is possible to define electoral support groups for such political parties based on the social, professional, and demographic characteristics. The cases of the “Alternative for Germany” and the “Austrian Freedom Party” analyzed in the article demonstrate that the latter statement is more likely to be true. Those support groups can be identified within the framework of the sociological theory of electoral behavior, as well as the theories of the losers of globalization by H. G. Betz and the cultural backlash of P. Norris and R. Inglehart, using the analysis of existing relevant statistics, mainly sociological surveys. The examples of Germany and Austria prove the assumptions that men, workers, people with no higher education and the unemployed are more likely to vote for right-wing populist parties.